Photonic crystal enhanced fluorescence using a quartz substrate to reduce limits of detection - Pokhriyal, Anusha (Optical Society of America, 2010)
A Photonic Crystal (PC) surface fabricated upon a quartz substrate using nanoimprint lithography has been demonstrated to enhance light emission from fluorescent molecules in close proximity to the PC surface. Quartz was selected for its low autofluorescence characteristics compared to polymer-based PCs, improving the detection sensitivity and signal-to-noise ratio (SNR) of PC Enhanced Fluorescence (PCEF). Nanoimprint lithography enables economical fabrication of the subwavelength PCEF surface structure over entire 1x3 in(2) quartz slides. The demonstrated PCEF surface supports a transverse magnetic (TM) resonant mode at a wavelength of λ = 632.8 nm and an incident angle of θ = 11°, which amplifies the electric field magnitude experienced by surface-bound fluorophores. Meanwhile, another TM mode at a wavelength of λ = 690 nm and incident angle of θ = 0° efficiently directs the fluorescent emission toward the detection optics. An enhancement factor as high as 7500 × was achieved for the detection of LD-700 dye spin-coated upon the PC, compared to detecting the same material on an unpatterned glass surface. The detection of spotted Alexa-647 labeled polypeptide on the PC exhibits a 330 × SNR improvement. Using dose-response characterization of deposited fluorophore-tagged protein spots, the PCEF surface demonstrated a 140 × lower limit of detection compared to a conventional glass substrate.